The lives of the popes (Religious Tract Society, 1850)
pt. I. From the rise of the Roman church to the age of Gregory VII. A.D. 100-1046.--pt. II. From the age of Gregory VII. to the dawn of the Reformation, A.D. 1046-1431.--pt. III. From the dawn of the Reformation to the Romanist re-action, A.D. 1431-1605.--pt. IV. From the Romanist re-action to Pope Pius the ninth, A.D. 1605-1852.